An Analysis on the Impact of Cash Conversion Cycle Dimension toward Return on Assets (ROA) (Studies in Food and Beverages Company Listed in Indonesia Stock Exchange (IDX) Year Period 2010-2012) - Khanifah Khanifah; Ulfi Amalia Fatkhurrohmah (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
This study aimed to examine the effect of dimensional analysis of the cash conversion cycle Return on Assets (ROA) (studies on food and beverages companies listed in Indonesia Stock Exchange (IDX) year period from 2010 to 2012). The independent variable in this study used the inventory conversion period, receivables collection period, and the period of suspension of debt, control variables in this study were the current ratio, laverage, and size, and the dependent variable in this study is ROA. This study used purposive sampling method in determining the number of samples used and acquired 20 companies were used as samples. This study uses regression analysis using the classical assumption pand using the software SPSS 17.00. The test results obtained with SPSS for the variable X1 (Inventory Conversion Period) that the inventory conversion period negative effect on ROA obtained t value = -6.588 with a significance level of 0.000. The test results obtained with SPSS for the variable X2 (Receivables Collection Period) that the Accounts receivable collection periods negatively affect ROA obtained t value = -9.761 with a significance level of 0.000. The test results obtained with SPSS for variable X3 (Debt Suspension Period) that the Debt deferral period has positive effect on ROA obtained t value = 3.949 with a significance level of 0.000. The test results obtained with SPSS for the variable X4 (Current Ratio) while the current ratio has a positive effect on ROA obtained t value of 2.571 with a significance level of 0.014. The test results obtained with SPSS for the variable X5 (Laverage) that the laverage negative effect on ROA obtained t value of -11.681 with a significance level of 0.000. The test results obtained with SPSS for variable X6 (Size) that the size has a positive effect on ROA obtained t value of 231.693 with a significance level of 0.000. Keywords: Conversion Period Inventory, Accounts Receivable Collection Period, Suspension Period payable, Current Ratio, Laverage, Size.